1
$\begingroup$

Simplify $$\frac{2\tan\left(\frac{x}{2}\right)}{\left(\tan\left(\frac{x}{2}\right)-1\right)^2} + \frac{\tan^2\left(\frac{x}{2}\right)+1}{2\tan\left(\frac{x}{2}\right)}$$

It should be like: $$\frac{2\sin(x) - 2\sin^2(x) - 2}{2(\sin(x)-1)\sin(x)}$$ I can use any trigonometric identities, for example: $$\tan\left(\frac{x}{2}\right)=\frac{1-\cos(x)}{\sin(x)} $$

$\endgroup$
1
$\begingroup$

Let $y=\dfrac x2$.

Then using the identities $$\sec^2y=1+\tan^2y\tag{1}$$ $$\sin 2y=2\sin y\cos y\tag{2}$$ the expression becomes $$\begin{align}\frac{2\tan y}{(\tan y-1)^2}+\frac{\tan^2y+1}{2\tan y}&=\frac{2\tan y}{\tan^2y+1-2\tan y}+\frac{\sec^2y}{2\tan y}\tag{1}\\&=\frac{\frac{2\sin y}{\cos y}}{\frac1{\cos^2y}-\frac{2\sin y}{\cos y}}+\frac{\frac1{\cos^2y}}{\frac{2\sin y}{\cos y}}\tag{1}\\&=\frac{2\sin y\cos y}{1-2\sin y\cos y}+\frac1{2\sin y\cos y}\\&=\frac{\sin2y}{1-\sin2y}+\frac1{\sin2y}\tag{2}\\&=\frac{\sin^22y-\sin2y+1}{\sin2y(1-\sin2y)}\\&=\frac{\sin^2x-\sin x+1}{\sin x(1-\sin x)}\\&=\boxed{\frac{2\sin x - 2\sin^2 x - 2}{2(\sin x-1)\sin x}}\end{align}$$ as you have stated.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.